2020
DOI: 10.3389/fmicb.2020.564513
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Hypochlorous Wound Irrigation Solutions Demonstrate Lower Anti-biofilm Efficacy Against Bacterial Biofilm in a Complex in-vitro Human Plasma Biofilm Model (hpBIOM) Than Common Wound Antimicrobials

Abstract: Biofilms pose a relevant factor for wound healing impairment in chronic wounds. With 78% of all chronic wounds being affected by biofilms, research in this area is of high priority, especially since data for evidence-based selection of appropriate antimicrobials and antiseptics is scarce. Therefore, the objective of this study was to evaluate the anti-biofilm efficacy of commercially available hypochlorous wound irrigation solutions compared to established antimicrobials. Using an innovative complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Even though several studies addressed this issue, most concluded that further analyses are mandatory to gain evidence-based recommendations for the daily use of antimicrobial dressings (Storm-Versloot et al, 2010;Daeschlein, 2013;Forster and Pagnamenta, 2015;Wu et al, 2015;Norman et al, 2016). Using a complex 3D model designed to mimic the micro-environment of a human wound biofilm (lhBIOM), composed of human material (plasma, platelets and leukocytes), this study aimed to extend the knowledge-base on efficacy profiles of antimicrobial wound dressings in a more transferable, "closer-to-reality" test scenario (Besser et al, 2020;Rembe et al, 2020;Stuermer et al, 2021). In this model, the incorporated bacteria encounter not only a milieu similar to the wound exudate (Loeffler et al, 2013), but also a certain immunological competence represented by leukocytes, so a biofilm matrix has to be produced under the challenge of a donor's immunocompetence (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though several studies addressed this issue, most concluded that further analyses are mandatory to gain evidence-based recommendations for the daily use of antimicrobial dressings (Storm-Versloot et al, 2010;Daeschlein, 2013;Forster and Pagnamenta, 2015;Wu et al, 2015;Norman et al, 2016). Using a complex 3D model designed to mimic the micro-environment of a human wound biofilm (lhBIOM), composed of human material (plasma, platelets and leukocytes), this study aimed to extend the knowledge-base on efficacy profiles of antimicrobial wound dressings in a more transferable, "closer-to-reality" test scenario (Besser et al, 2020;Rembe et al, 2020;Stuermer et al, 2021). In this model, the incorporated bacteria encounter not only a milieu similar to the wound exudate (Loeffler et al, 2013), but also a certain immunological competence represented by leukocytes, so a biofilm matrix has to be produced under the challenge of a donor's immunocompetence (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral resistance gene transfer between species and sub-species, dorment persister cells in the depth of biofilm and tissue as well as an effective biochemical diffusion barrier for active agents are further aspects contributing to the high resilience of microbial biofilms (Percival et al, 2015;Kirketerp-Møller et al, 2020). Even if an antimicrobial substance is capable of effectively eradicating a bacterial strain in its planctonic state, a deep enough penetration to achieve the same reductive efficacy, cannot be ensured in a complex biofilm scenario (Rembe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies can be due to using various methods and different concentrations of NaOCl and HOCl. While the antimicrobial activity of high chlorine concentrations is undisputable, the extrapolation of favorable results to all SOH-containing products (regardless of the chlorine content) seems to be inappropriate [ 27 , 79 , 80 , 81 , 82 , 83 ]. There is a lack of evidence for a prolonged time of action of SOH.…”
Section: Introductionmentioning
confidence: 99%
“…Further, classical in vitro models often expose established microbial biofilms in environmental conditions that are divorced from the host context. For example, host-derived biofilm components such as fibrin and leukocyteassociated proteins can alter biofilm composition and structure (Besser et al, 2020;Kwiecinski et al, 2016;Nett et al, 2015;Rembe et al, 2020), with potential effects on antiseptic susceptibility, virulence and pathogenesis. Our model provides a clinically-relevant environmental context for microbial growth.…”
Section: Discussionmentioning
confidence: 99%